Infrapatellar Fat Pad Impingement: A Systematic Review - Genin, Jason; Faour, Mhamad; Ramkumar, Prem N.; Yakubek, George; Khlopas, Anton; Chughtai, Morad; Mont, Michael A.; King, Dominic (The Journal of Knee Surgery, 2017)
Infrapatellar fat pad impingement represents a source of anterior knee pain that is often overlooked. Due to the scarcity of reports related to this disorder, we conducted a systematic review of the literature related to infrapatellar fat pad impingement in evaluating the following: (1) clinical presentation, (2) imaging, (3) management, and (4) clinical outcomes. A systematic review was conducted investigating all available primary literature related to the clinical presentation, imaging, management, and outcomes of infrapatellar fat pad impingement syndrome. A total of 15 studies (9 case reports, 1 case series, and 5 retrospective studies) comprising 167 patients met eligibility criteria for this review. Patients with infrapatellar fat pad impingement were found to most often present with anterior knee pain that worsened with activity, and was frequently associated with trauma. Anterior knee pain, tenderness to palpation over the patellar tendon, loss in terminal extension, and pain with direct pressure on the medial or lateral side of the patella with the knee extended was often found on examination. Although patients may have classic imaging findings on magnetic resonance imaging (localized edema of the infrapatellar fat pad, deep fluid-filled infrapatellar bursa, nonvisualization of clefts, fibrosis, and calcifications), not all patients had positive imaging findings, thus making infrapatellar fat pad impingement a clinical diagnosis. Treatment begins with nonoperative management, but in recalcitrant cases, patients can be surgically treated with arthroscopic fat pad resection. Most patients who undergo operative treatment report improvement or complete resolution of symptoms in terms of pain and range of motion, and are able to return to work. To the best of our knowledge, this is the first comprehensive review on infrapatellar fat pad impingement to better aid the orthopaedic surgeons in diagnosing, treating, and managing patient expectations for this often overlooked knee pathology.
Keywords: knee; fat pad; impingement; infrapatellar fat pad